Leveraging prospective teachers’ knowledge through their participation in lesson study - González, Gloriana; Villafañe-Cepeda, Wanda; Hernández-Rodríguez, Omar (Journal of mathematics teacher education, 2023)
This study focuses on a lesson study adaptation for bridging prospective teachers’ experiences in a methods course and their field experiences in a teacher education program in Puerto Rico. We ask, what opportunities for teacher learning emerge during discussions in lesson study? Two lesson study teams of secondary mathematics prospective teachers, each led by an experienced mentor, planned technology-based lessons . Using the theoretical framework for lesson study by Lewis and colleagues, we analyzed video recordings of the teams’ discussions. The results show learning opportunities in the three dimensions of the framework: teachers’ knowledge and beliefs , the creation of a professional community , and the development of teaching–learning artifacts . The mentors leveraged prospective teachers’ knowledge, built on topics discussed in the methods course, and created a professional learning community. Three resources introduced in the methods course supported the creation of a hybrid space connecting academic and practitioner knowledge: shared language about teaching moves for using technology in math instruction, the mathematical proficiency framework, and a lesson plan template. The mentors drew upon their subject matter and pedagogical knowledge during their facilitation of lesson study. The intervention exemplifies a lesson study adaptation that is feasible in the context of a teacher education program.